Digital marketing practices in Iceland - Björgvin Jóhannsson 1979- (2014)
As consumers are moving towards the digital media at an increasing rate marketers must follow. Past research has indicated that Icelandic marketers are lagging behind regarding their digital marketing practices. The purpose of this thesis was to offer insight into the digital marketing practice in Iceland on the basses of best practice according to the available literature assess the trends and where digital marketing headed. With this information, Icelandic marketers should be able to better organize their overall marketing strategy. A qualitative research design was chosen due to the lack of available research data on the subject. Data was gathered via semi-structured interviews in order to gain a better insight into the opinions of the marketers themselves. Every digital platform was covered, what they are, how they work and how to use them ending in a best practice recommendation according to the available literature. The results indicate that the Icelandic marketers seem too vary in their approach to digital marketing practices. There are marketers that are applying best practice and there are also companies that confirm the notion that Icelandic marketers lack knowledge of the digital marketing media.